Overall Indoor Quality of a Non-renewed Secondary-school Building. (November 2015) - Loreti, Lisa; Barbaresi, Luca; De Cesaris, Simona; Garai, Massimo
Abstract: This work is the result of a field study about overall comfort aspects performed in a secondary-school building during the winter season. The campaign aimed at describing the conditions of the school both from an objective and a subjective point of view, thus a questionnaire was administered to pupils during ongoing lessons. The monitored attributes concerned typical indoor quality aspects: acoustical, thermal, indoor air and visual quality. Weak points emerged from the data analysis and possible solutions are illustrated, focusing in particular on the acoustic aspects.